IMPROVING THE FINANCING OF THE PURCHASE OF FOOD PRODUCTS FOR THE IMPROVEMENT OF STANDARDS AT THE UNIVERSITY OF DEFENCE - Knežević, Milena; Janković Šoja, Svjetlana; Milunovic, Milan (Economics of Agriculture, 2024)
This paper analyses financial resources for procuring agricultural products at the University of Defense as an organizational part of the Ministry of Defense of the Republic of Serbia. The physical condition of students and cadets is crucial because it affects the overall operational capability of the Army of the Republic of Serbia. Therefore, this paper points out the weaknesses and shortcomings in the supply of food products for nutrition needs. This paper analyzes data for the procurement of items by category in the period from 2018 to 2020, as well as the expenditure of funds by groups of things in the period from 2010 to 2021 to ensure the proper nutrition of students and cadets of the University of Defense. The SPSS software was used to analyse the tendency of spending financial resources. It is concluded that the main problem is the inconsistency of budget procedures with public procurement.